A model of Russia's "virtual economy" - R.E. Ericson; B.W. Ickes (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
The Russian Economy has evolved into a hybrid form, a partially monetized quasi-market system that has been called the virtual economy.In the virtual economy, barter and non-monetary transactions play a key role in transferring value from productive activities to the loss-making sectors of the economy.We show how this transfer takes place, and how it can be consistent with the incentives of economic agents.We analyze a simple partial-equilibrium. model of the virtual economy, and show how it might prove an obstacle to industrial restructuring and hence marketizing transition.
URN:NBN:fi:bof-201408072119
Keywords: 330